2022
DOI: 10.31635/ccschem.021.202101042
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundaries Engineering of Hollow Copper Nanoparticles Enables Highly Efficient Ammonia Electrosynthesis from Nitrate

Abstract: Electrochemical nitrate (NO 3 -) reduction reaction (NO 3 -RR) represents as an ideal route for the production of ammonia (NH 3 ) under ambient conditions. Although a markedly improved NH 3 production rate has achieved on the NO -RR than the nitrogen reduction reaction (NRR), the NH 3 production rate of NO 3 -RR is still well below the industrial Haber−Bosch route due to the lack of robust electrocatalysts for yielding high current densities with concurrently good suppression of hydrogen evolution reaction (HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…These results can be explained by the unsaturated coordination environment due to the presence of grain boundaries, which can alter the electronic structure of central Bi atoms and promote the electron transfer from Bi atoms to oxygen atoms of *OCHO. [ 25,42 ] Taken together, it can be reasonably concluded that the introduction of grain boundaries can enhance the CO 2 adsorption capacity and promote/stabilize the subsequent *OCHO intermediate formation, synergistically contributing to significantly enhanced CO 2 RR performance.…”
Section: Resultsmentioning
confidence: 96%
“…These results can be explained by the unsaturated coordination environment due to the presence of grain boundaries, which can alter the electronic structure of central Bi atoms and promote the electron transfer from Bi atoms to oxygen atoms of *OCHO. [ 25,42 ] Taken together, it can be reasonably concluded that the introduction of grain boundaries can enhance the CO 2 adsorption capacity and promote/stabilize the subsequent *OCHO intermediate formation, synergistically contributing to significantly enhanced CO 2 RR performance.…”
Section: Resultsmentioning
confidence: 96%
“…40 According to previous reports, the C s value used for this calculation is 0.04 mF cm −2 . 40,50 As displayed in Figure S9, the Fe 0.5 Mo 0.1 V 0.4 /NF electrode still possesses the highest specific activity among all as-prepared catalysts, further suggesting that ECSA is not the key factor for enhanced OER activity.…”
Section: Resultsmentioning
confidence: 96%
“…The ECSA was calculated based on the C dl according to the equation: ECSA = C dl / C s , where C s is the capacitance of an atomically smooth planar surface of the material per unit area . According to previous reports, the C s value used for this calculation is 0.04 mF cm –2 . , As displayed in Figure S9, the Fe 0.5 Mo 0.1 V 0.4 /NF electrode still possesses the highest specific activity among all as-prepared catalysts, further suggesting that ECSA is not the key factor for enhanced OER activity.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the competitive cathodic hydrogen evolution reaction (HER) also affects the faradaic efficiency (FE) of NH 3 production via eight-electron reduction of nitrate. [24,25] Therefore, to suppress N 2 formation and HER, the design and development of electrocatalysts with good activity, selectivity and stability is desirable yet challenging.…”
Section: Doi: 101002/smll202203335mentioning
confidence: 99%